Engenharia de defeitos em semicondutores de gap largo - Herval, Leonilson Kiyoshi Sato de (2015)
Defects play a fundamental issue on physical properties of wide bandgap semiconductors (WBS) due to the possibility of application in high temperature. This work shows the features of the defects in di erent kind of WBS grown/synthesized by solid state reaction, Pechini method and Molecular Beam Epitaxy. First we investigated the structural and optical properties of erbium- and manganese-doped strontium aluminates (SrAl2O4). The fundamental optical transitions due to Er3+ and Mn2+ are typical features of the well-diluted doping process. A signi cant enhancement of the Er3+ optical emission band at 1530 nm was observed when the matrix is co-doped with Mn. A model of energy transfer mechanism from Mn2+ to Er3+ is proposed to explain the experimental results. We present also the e ect of preparation and annealing conditions on the properties of Nb2O5. The increase of oxygen vacancies causes an inrreversible phase transition from pseudohexagonal to orthorhombic phase, and they are responsible for the increase in the e ective magnetic moments related to paramagnetic behavior. Finally, we explore the e ects of the interfaces imperfections of quantum wells of cubic GaN alloys. An indication of localized states in low temperature is observed. A decrease of this e ects happens when we increase the number of interfaces. Furthermore, magneto-PL measurements show a higher spin polarizations in the donor-acceptor impurities in the bulk of c-GaN corroborate for the importance of the defects. This work shows that the defects engineering in WBS are fundametal for developing new technologies in spintronics and optoelectronic eld.